Electrical characterization of aluminum (Al) thin films measured by using four- point probe method - Pant, GD; Subedi, DP (Kathmandu University Journal of Science Engineering and Technology, 2013)
This paper reports the results of electrical characterization of aluminum thin films. Uniform Al thin films were deposited by physical vapor deposition (PVD) technique on glass substrates. The electrical resistivity of the films as a function of film thickness was studied. These parameters have been measured by four-point probe method. The electrical resistivity was obtained by the measurement of current (in mA) and voltage in (mV) through the probe. The results showed that resistivity of the film decreases linearly with the film thickness in the range of the thickness studied in this work.